Students’ creative thinking in physics: An investigation of the effectiveness of the CPS instructional model - Ena, Suma Indrawati; Zaturrahmi, Zaturrahmi; Dini, Kenmandola (International Journal of Innovative Research and Scientific Studies, 2025)
This experimental study investigates the effectiveness of the Creative Problem Solving (CPS) instructional model in enhancing creative thinking skills among high school physics students, with particular focus on the challenging topic of sound waves. Employing a rigorous quasi-experimental design with pretest-posttest control group methodology, the research involved 60 eleventh-grade students from SMAN 5 Padang, Indonesia, evenly divided into experimental and control groups. The experimental group participated in CPS-based learning activities that emphasized problem exploration, idea generation, and solution refinement, while the control group received conventional teacher-centered instruction. Quantitative analysis revealed statistically significant improvements in the experimental group’s creative thinking scores (M=73.83) compared to the control group (M=60.43), with a strong t-test result (t=9.76, p<0.05). The intervention yielded a moderate normalized gain score (g = 0.50) and a remarkably large effect size (d = 2.59), particularly in the creative thinking indicators of fluency (the ability to generate multiple ideas) and flexibility (the capacity to approach problems from diverse perspectives). Complementary qualitative data from classroom observations and student interviews provided rich insights into the learning process, documenting enhanced student engagement, increased confidence in expressing novel ideas, and greater willingness to explore unconventional solutions to physics problems. Students reported appreciating the structured yet open-ended nature of CPS activities, which allowed them to connect abstract sound wave concepts to real-world applications. These compelling findings position CPS as a valuable pedagogical approach for physics education, effectively bridging the gap between content mastery and the development of creative skills.